An insight on the key factors influencing the accuracy of the actuator line method for use in vertical-axis turbines: Limitations and open challenges. (15th October 2022) - Mohamed, Omar S.; Melani, Pier Francesco; Balduzzi, Francesco; Ferrara, Giovanni; Bianchini, Alessandro
Graphical abstract: Highlights: Insight on the key factors affecting accuracy of ALM for VAWTs. Frozen ALM + blade-resolved CFD to understand current limitations. Kernel shape/size do not affect significantly accuracy. Mesh size in the wake is key for a good resolution. Dynamic stall modeling is the key factor determining accuracy. Abstract: Darrieus vertical-axis turbines are known for their complex aerodynamics connected to the continuous change in the angle of attack experienced by the blades, which often exceeds the static stall limit. Low fidelity tools such as the Blade Element Momentum Theory have been shown lately not to provide sufficient levels of accuracy, while the medium-fidelity Actuator Line Method (ALM) has been increasingly applied to Darrieus rotors. In this method, the blade-flow interaction is modeled as an equivalent momentum loss calculated introducing equivalent aerodynamic forces into the computed Computational Fluid Dynamics (CFD) domain. This strongly reduces the computational cost in comparison to blade-resolved CFD, allowing ALM to be used in three-dimensional problems, e.g., multiple rotors, floating offshore, etc. While several corrections and guidelines have been recently proposed to tailor ALM to Darrieus turbines, issues are still open on how to improve accuracy. The present study aims at assessing to what extent the three main factors of the ALM theory, namely the quality of input polar, the dynamic stall modeling, and the force insertion in the domain, influence the overall accuracy of the method. In particular, this unprecedented understanding is enabled by the novel use of a "frozen ALM", i.e., an ALM method fed by the aerodynamic forces calculated by blade-resolved CFD, which allowed to separate the contributions coming from airfoil performance analysis and force projection in the domain. Based on the results, three main important conclusions are drafted out: i) for high and medium tip-speed ratios, provided that the aerodynamic forces are correct, the ALM method is able to generate extremely accurate solutions of the flow field, almost equivalent to blade-resolved CFD; ii) the relevance of the kernel's shape and smearing function is largely overestimated and current knowledge is adequate for the model to be set; iii) a better dynamic stall model is indeed the real key factor that could lead to an improvement of the ALM accuracy.